المرافقة النفسية للأمهات أطفال داء السكري دراسة 06 حالات بالأغواط - رجم نبيلة; سعداوي فريحة; خوحلي أحلام (My University, 2023)
The current study aimed to identify the nature of the psychological pension for mothers with children with chronic diabetes, knowing that the psychological accompanying pension is the basic essence that represents psychology; The patient achieved the objectives of the study and then relied on the clinical approach, a case study, and we also used a main tool, which is the interview after collecting information and applying the Beck scale for depression and the David Son scale for trauma, for mothers, so that the research group had (6) three cases of their children with diabetes, and through what We concluded from the results of our research that the lack of psychological support during the discovery of the disease in sick mothers and children led them to psychological trauma and depression and not accepting their children's illness. And it became clear that the level of depression and trauma is between the severe and medium level, and this is due to a number of factors, the most important of which is the lack of psychological support for mothers and the affected child